Analysis of water quality under different hydrologic regimes in Saigon River, Vietnam - Tran Nguyen Thien An; Babel, Mukand Singh; Clemente, Roberto S.; Sutat Weesakul; Thammarat Koottatep; Deutscher Akademischer Austausch Dienst (DAAD),Germany; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
This study was conducted to analysis the water quality of the estuary region, the study area was chosen in Saigon River Basin which is one of the most important river basin as the biggest city of Vietnam named Ho Chi Minh City located in. The secondary water quality data was graphical and statistical analysis and the study has improved that Saigon River{u2019}s water quality was worse at the downstream part but the water quality become to be better near the river mouth as the result of better inflow from Dongnai River. Moreover, the water quality of Saigon River in the last 10 years was lower than the Vietnamese standard named 5942-1995 (category B) except TSS concentration. The Pearson{u2019}s correlation was applied for the relationship between precipitation and discharge with water quality show weak to fair correlation (0.29 {u2013} 0.599). The PCA/FA expressed the factors which most affect to the water quality of this river were: anthropogenic activities, natural affections, biological (Coliform and E-Coli) and heavy metal were the two more detail explanations for municipal and industrial activities. The MIKE 11 water quality model was applied successfully to simulation the variation of DO and BOD5 concentration in Saigon River. The scenarios of changes in upstream releases and increase downstream water level as the effluence of sea level rise were applied to calibrated model showed the considered affection to water quality by the changes of upstream releases. The increase of water level and increase in upstream releases made the water quality of river to be better while the decrease of upstream release reduced the quality of the river. The results of the study can be applied to the management planning purpose for Saigon river basin further study on water quality and the calibrated water quality model can be applied in many others research concerned with the Saigon River{u2019}s water quality. Especially, this result can be applied for the water quality protection program of Ho Chi Minh City as an initial assessment by statistical and modeling tools in water quality.
A thesis submitted in partial fulfillment of the requirements for theWater Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Water quality -- Vietnam -- Saigon River